A STUDY OF RISK TRANSFER ON TOLL ROAD OPERATION IN INDONESIA BY CIVIL ENGINEERING COMPLETED RISKS INSURANCE (CECR) - JANUS MANGAPUL GULTOM (NIM 25004034), RICKY
The implementation of toll road serves the purpose to increase the efficiency of distribution service, which in turn will sustain the improvement of economic growth especially in those areas which has been well developed. To assure that this purpose consistently achieved, the effective and efficient risk management is an essential issue. One way to do this is through risk transfer. By transferring the risk, the level of risk exposure can be reduced, and this can be done alternatively by insurance mechanism. Insurance mechanism becomes an important alternative to consider in the toll road implementation, when the loss potential caused by the failure of performing toll road function is hard to control by other risk management methods. This research is intended to study the risk transfer mentioned above by means of Civil Engineering Completed Risks (CECR) -a policy which is designed to cover up the risk of infrastructure damages on the operational phase- which in the process includes a series of identifying dan classifying risks exposed in the toll road operation, and transferring those risks with CECR policy. Furthermore, the process includes analyzing the risks covered in CECR policy with the risks identified in this research and the practice in some cases of Indonesian toll road. The research methods used in this research are literature study, survey, interview and spreading questionnaires. The risk identification developed in this research has not yield risk factor which is mutually exclusive and collectively exhaustive variable. The classification give in 13 primary risk factors in toll road operation, and risk transfer mechanism through CECR policy cover up 4 of these factors. Whereas CECR policy (basic and additional coverage) can transfer 33.15% of total risk value that's been identified. This risk fator transfer gives the toll road operator a flexibility to manage the remaining risk factors by other risk management alternatives. The research findings can be used by toll road operator to consider insurance mechanism as a way of risk transferring into the toll road risk management plan. Aside from this, this research can serve as a reference for further researches focusing on finding a balanced premium sharing between the stakeholders involved in toll road operation.